Unaffected features of BSA stabilized Ag nanoparticles after storage and reconstitution in biological relevant media - Valenti, Laura Elisa (2015)
Silver-coated orthopedic implants and silver composite materials have been proposed to produce local biocidal activity at low dose to reduce post-surgery infection that remains one of the major contributions to the patient morbidity. This work presents the synthesis combined with the characterization, colloidal stability in biological relevant media, antimicrobial activity and handling properties of silver nanoparticles (Ag-NP) before and after freeze dry and storage. The nanomaterial was synthesized in aqueous solution with simple, reproducible and low-cost strategies using bovine serum albumin (BSA) as the stabilizing agent. Ag-NP were characterized by means of the size distribution and morphology (UV-vis spectra, dynamic light scattering measurements and TEM images), charge as a function of the pH (zeta potential measurements) and colloidal stability in biological relevant media (UV?vis spectra and dynamic light scattering measurements). Further, the interactions between the protein and Ag-NP were evaluated by surface enhanced Raman spectroscopy (SERS) and the antimicrobial activity was tested with two bacteria strains (namely Staphylococcus aureus and Staphylococcus epidermidis) mainly present in the infections caused by implants and prosthesis in orthopedic surgery. Finally, the Ag-NP dispersed in aqueous solution were dried and stored as long-lasting powders that were easily reconstituted without losing their stability and antimicrobial properties. The proposed methods to stabilize Ag-NP not only produce stable dispersions in media of biological relevance but also long-lasting powders with optimal antimicrobial activity in the nanomolar range. This level is much lower than the cytotoxicity determined in vitro on osteoblasts, osteoclasts and osteoarthritic chondrocytes. The synthesized Ag-NP can be incorporated as additive of biomaterials or pharmaceutical products to confer antimicrobial activity in a powdered form in different formulations, dispersed in aqueous and non-aqueous solutions or coated on the surface of different materials.